TB in paediatric kidney transplant recipients – A single‐centre experience. (16th September 2021) - Makanda‐Charambira, Privilage D.; Nourse, Peter; Luyckx, Valerie A.; Coetzee, Ashton; McCulloch, Mignon I.
Abstract: Background: TB remains a major challenge in transplantation, particularly in endemic countries. This study aimed to describe the incidence, clinical presentation and outcomes of TB in paediatric kidney transplant recipients and to assess the impact of INH prophylaxis. Methods: Single‐centre retrospective descriptive analysis of children who received kidney transplants from 1995 to 2019 was carried out. The cohort was stratified according to receipt of INH prophylaxis which began in 2005. Results: A total of 212 children received a kidney transplant during the study period. Median age at transplantation was 11.2 years (IQR: 2.2–17.9), and 56% were males. TB was diagnosed in 20 (9%) children, with almost two‐thirds ( n = 12) occurring within the first year. Most infections were pulmonary. The main presenting symptoms included fever ( n = 13/20), weight loss ( n = 12/20) and cough ( n = 10/20). TST was positive in four of 20 children. Coinfection with EBV, CMV or Staph was found in five children. Due to drug interactions, an up to threefold increase in calcineurin inhibitor dose was required to maintain therapeutic blood levels. INH prophylaxis was protective against development of TB ( p = .04). Gender, age and type of allograft were not significant risk factors. Graft and patient survival was 100% upon completion of TB treatment. Conclusion: Kidney transplant recipients in endemic countries have a high risk of developing TB. Diagnosis remains a challenge. Frequent and meticulous monitoring of immunosuppression drug levels during treatment of TB is required to avoid loss of patient or graft. INH prophylaxis protects against development of TB in this population.